PERENCANAAN PENERAPAN APLIKASI WEB 2.0 UNTUK PEMBELAJARAN ORGANISASI DI PERPUSTAKAAN UNIVERSITAS PENDIDIKAN INDONESIA - Santika, Santi; Mulyono, Pudji; Hermadi, Irman (Edulib, 2017)
Library of Universitas Pendidikan Indonesia (UPI) has a quality policy commitment to continuous improvement in every area and process. It can be achieved by continuously optimizing organizational learning. Web 2.0 is a media application that can help the organizational learning process because it has the characteristics of read and write, as well as having the flexibility of time use, but the application must be in accordance with the culture and character of the organization. Therefore, this study aimed to find out the Web 2.0 application that can be applied to the organizational learning in the Library of UPI. The method used is a mixed method qualitative and quantitative approach. Research stage refers to the stage of planning and support phases of Web 2.0 Tools Implementation Model. The results showed that the application of Web 2.0 can be applied to the organizational learning in the Library UPI. It refers to the tendency of organizational culture Library of UPI that is good and tendency of HR Library UPI attitude against the use of the Internet and computers are very good. Web 2.0 applications that can be used by UPI library are blogs, online forums, and wiki as a primary tools. Facebook, Youtube, chat application, twitter and Instagram as a supporting tools.